2006
DOI: 10.1097/01.aco.0000236143.61593.14
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia drugs, immunity, and long-term outcome

Abstract: Long-term outcome after surgery is a new safety concern in perioperative care. We are faced with enormous challenges in healthcare and research. As providers, tailoring an anesthetic plan to patients' needs will become increasingly critical, and immunology should help in this pursuit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
64
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 60 publications
0
64
0
2
Order By: Relevance
“…The severity and duration of surgical trauma, patients' age, and anesthetic methods may influence perioperative stress response. [4][5][6][7][8][9] Anesthesia maintains homeostasis, makes the operation painless, reduces excessive response to surgery, and modulates immune responses. [10] In addition, anesthetics influence cellular (the functions of immune competent cells) and humoral (inflammatory mediator gene expression and secretion) inflammatory responses.…”
mentioning
confidence: 99%
“…The severity and duration of surgical trauma, patients' age, and anesthetic methods may influence perioperative stress response. [4][5][6][7][8][9] Anesthesia maintains homeostasis, makes the operation painless, reduces excessive response to surgery, and modulates immune responses. [10] In addition, anesthetics influence cellular (the functions of immune competent cells) and humoral (inflammatory mediator gene expression and secretion) inflammatory responses.…”
mentioning
confidence: 99%
“…Therefore, the neuroen docrine system and proinflammatory cytokines and antiinflammatory cytokines synergistically augment their suppressive effects in the perioperative immune system. Interleukin6 (IL6) is an important media tor of the acute phase response and a sensitive mark er of tissue damage (7). The surgicalstressinduced release of hormones such as catecholamines (nore pinephrine and epinephrine), adrenocorticotropic hormone (ACTH) and cortisol via the autonomic nervous system and the HPA mediates inhibitory effects on immune functions (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Inhalant anesthetics induce dose-dependent respiratory depression, lead to arterial pressure reduction and potential cardiac arrhythmias, and are known to influence the immune system as well. Volatile anesthetics appear to suppress the effectors' functions of both innate and adaptive immunity, assist tumor growth in animal models, and facilitate aggregation of certain neurodegenerative disease proteins (HOMBURGER and MEILER, 2006). It has been demonstrated that anesthetic agents given during any procedure may lead to immunosuppression (KELBEL and WEISS, 2001).…”
mentioning
confidence: 99%